1986
DOI: 10.1002/aja.1001770112
|View full text |Cite
|
Sign up to set email alerts
|

Stereological analysis of peroxisomes and mitochondria in intestinal epithelium of patients with peroxisomal deficiency disorders: Zellweger's syndrome and neonatal‐onset adrenoleukodystrophy

Abstract: Peroxisomes, participants in lipid metabolism, have been shown to be altered in liver in two metabolic diseases in which long-chain fatty acids accumulate in tissues: Zellweger's syndrome and neonatal adrenoleukodystrophy (ALD). The intestine also plays a role in lipid metabolism, and we have had the opportunity to compare peroxisomes in normal intestinal epithelium with those from patients with Zellweger's syndrome and neonatal ALD at the electron microscopic level by using the combined techniques of cytochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…These authors suggested that the ghosts represented PO membranes which could not import the matrical proteins because of defects in the translocation machinery. Moreover, long sinuous tubules with positive DAB content were described in the intestinal epithelial cells of a patient with neonatal adrenoleukodystrophy (11). The possible relationship of the ghost-like structures in fibroblasts and the sinuous tubules in intestinal epithelial cells with the double-membraned loops noted in the present study deserves further investigation.…”
Section: Alterations Of the Po Membranesupporting
confidence: 61%
“…These authors suggested that the ghosts represented PO membranes which could not import the matrical proteins because of defects in the translocation machinery. Moreover, long sinuous tubules with positive DAB content were described in the intestinal epithelial cells of a patient with neonatal adrenoleukodystrophy (11). The possible relationship of the ghost-like structures in fibroblasts and the sinuous tubules in intestinal epithelial cells with the double-membraned loops noted in the present study deserves further investigation.…”
Section: Alterations Of the Po Membranesupporting
confidence: 61%
“…Lazarow et al [27] mentioned the existence of round and elongated peroxisomes in the small intestine of a normal child. In the stereological analysis of peroxisomes in intes tinal epithelium of patients with Zellweger's syndrome and neonatal-onset adrenoleukodystrophy by Black and Cornacchia [11], the presence of tubular forms is obvious in chil dren. Roels et al [28] performed a detailed morphometric study of the two peroxisomal populations in human adult intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that peroxisomal altera tions have been reported in the intestinal epi thelium of neonates with Zellweger's syn drome and adrcnoleukodystrophy [11], to our knowledge no studies have been devoted to peroxisomes during the development of the human fetal intestine in contrast to the devel opment of the liver [12][13][14][15][16][17] and kidney [18], Therefore, the purpose of the present in vestigation was to analyze the ontogenesis, distribution and enzyme expression of intesti nal peroxisomes from 11-to 22-week human fetuses.…”
Section: ]mentioning
confidence: 99%
“…Morphologically recognizable peroxisomes were first reported missing in the liver and kidney of patients with the genetic disease, Zellweger syndrome, by Goldfischer et al (1973). A deficiency of peroxisomes in a variety of cell types from Zellweger patients has been widely confirmed, although a few residual peroxisomes have occasionally been noted (Arias et al, 1985;Black and Cornacchia, 1986;Lazarow and Moser, 1989). Consistent with the apparent absence of the organelle, many peroxisomal enzymes are missing (Tager et al, 19851, even though they are synthesized normally (Schram et al 1986).…”
mentioning
confidence: 99%